2023
DOI: 10.1159/000531378
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of CT-Guided Kidney Biopsy for the Diagnosis of Glomerular Diseases in Complicated Patients

Abstract: <b><i>Introduction:</i></b> Kidney biopsy is the cornerstone for the diagnosis of glomerular diseases and to guide treatment. Percutaneous ultrasound-guided kidney biopsy is currently the gold standard to obtain cortical specimens. However, in cases where ultrasound-guided kidney biopsy is not deemed safe (obese patients, deep kidneys, or kidneys with a complicated anatomy), CT-guided kidney biopsy could be a convenient alternative to obtain renal tissue samples. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In the study conducted by Javier Vian and colleagues, it showed a similar diagnostic rate to that of PKB (92.9% vs. 90.8%, p = 0.437). Additionally, there was no significant increase in the incidence of severe complications, including post-biopsy hypotension (1.8% vs. 2.5%, p = 0.621) and blood transfusion (0% vs. 4.3%, p = 0.122) [ 12 ]. Moreover, it demonstrated excellent sensitivity in detecting small perinephric hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Javier Vian and colleagues, it showed a similar diagnostic rate to that of PKB (92.9% vs. 90.8%, p = 0.437). Additionally, there was no significant increase in the incidence of severe complications, including post-biopsy hypotension (1.8% vs. 2.5%, p = 0.621) and blood transfusion (0% vs. 4.3%, p = 0.122) [ 12 ]. Moreover, it demonstrated excellent sensitivity in detecting small perinephric hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, when the kidney cannot be adequately visualized by ultrasound, e.g., in cases of extreme obesity, or in instances of complicated anatomy, e.g., bilateral cysts, the biopsy can alternatively be performed CT-guided [74,75]. CT guidance may allow a more precise biopsy needle placement in individual cases and has been shown to provide a high diagnostic yield in patients previously rejected for an ultrasound-guided biopsy [76].…”
Section: Performing the Biopsymentioning
confidence: 99%